Integrated application for automatic schedule-based distribution and monitoring of irrigation by applying the waterfall model process - Aulia Naufal Afif; Fiftin Noviyanto; Sunardi Sunardi; Son Ali Akbar; Eko Aribowo (Bulletin of Electrical Engineering and Informatics, 2020)
40% of areas in Indonesia are still using rainwater as a source for irrigation. Type of wetland rainwater always depends on weather that is currently difficult to predict. In addition, the frequency of field cultivation became limited. Irrigation water can come from a dam or a spring in the mountains. Limited water source generates the need to manage water distribution in all areas of rice fields. For every 1 hectare fields, at least 0.5 litres of water per second is needed. The imbalance between the field and the available water discharge can cause conflicts in the Community farmers manage field. The purpose of this research is to assist in the Assembly Of Farmer Water users ("Perkumpulan Petani Pemakai Air" or "P3A") manage the scheduling and controlling irrigation sluice based IoT using mobile applications. The waterfall process model applied in developing mobile applications. Every feature that is created has been tested directly using Unit tests based on the application of the system used. The test is done by observing the system inputs and outputs of the system usability scale (SUS). Tests are also carried out using Post-Study with method of the SUS.